The Effect of Discovery Learning Method Application on Increasing Students’ Listening Outcome and Social Attitude - Hanafi, Hanafi (Dinamika Ilmu, 2016)
Curriculum of 2013 has been started in schools appointed as the implementer. This curriculum, for English subject demands the students to improve their skills. To reach this one of the suggested method is discovery learning since this method is considered appropriate to implement for increasing the students’ ability especially to fulfill minimum criteria of success at school. This study is experimental study with one group pretest-posttest design. Its purpose is to know whether or not discovery learning model implementation could increase students’ listening score and social attitude in accordance with curriculum implementation. The subjects of this study are 37 students of class X IPA 5 Public High School 2 Jember in their 2nd semester of 2015/2016 academic year. The method used to collect data in the study is test. The research design is one group pretest-posttest design where there is only one group receiving the treatment which result is assessed by pre-test and post-test. The finding shows that there are improvement of both students’ listening and attitude scores. Based on data analysis it is concluded that the implementation of discovery learning model could increase students’ listening score and social attitude, with significance value of 0,005 (z = -2,823, p < 0,001), with medium effect size for listening score and significance value of 0,000 (-4,875, p < 0,001), with large effect size for social attitude.